Advanced Analysis of the Water/Fat Distribution in Skeletal Muscle Tissue Using Magnetic Resonance Imaging in Patients With Neuromuscular Disease - Nasel, Christian; Klickovic, Uros; Cetin, Hakan; Struhal, Walter; Moser, Ewald (Frontiers in Physics, 2020)
Purpose: Neuromuscular diseases (NMD) frequently cause severe disability. Magnetic resonance imaging (MRI) based calculation of the so-called fat fraction (FFR) in affected muscles was recently described as reliable biomarker for monitoring progression of NMDs. This is of high interest as newly available modern gene therapies, currently subject to intensive investigations, may provide at least palliation of these severely disabling diseases. In this retrospective study feasibility of advanced image analysis potentially extending the possibilities of using FFR in lower limbs in patients suffering various NMDs was investigated. Methods: Patients receiving MRI due to manifestation of proven NMDs (amyotrophic lateral sclerosis [n=6], spinobulbar muscular atrophy [n=4], limb girdle muscular dystrophy [n=5], metabolic myopathy [n=2]) in lower limbs were compared to patients without NMD [n=9]. We used both, the correlation of FFR and advanced parameters with clinical grades of strength obtained using the MRC-scale (Medical Research Council for Muscle Strength). In contrast to FFR, displaying the fat partition in muscles only, the full image information gained by MRI was transformed into standardised MRI-feature based matrices and Principal (PCA) and Independent Component Analysis (ICA) were employed to define parameters describing the full data obtained in more detail. Results: PCA- and ICA-based full image parameters remained strongly correlated to FFR (Spearman coefficient 0.96 – 0.59), but generally showed stronger correlations with the MRC-score in lower limbs (Spearman coefficient; FFR= -0.71; PCA & ICA parameters = -0.76 – -0.78). Age was no significant confounder in full image-assessment. Conclusion: While effectively extending the information gained by FFR the proposed advanced image analysis in NMDs is technically feasible and, so far, appears robust to age related effects.